More anterior bone loss in middle vertebra after contiguous two-segment cervical disc arthroplasty - Minghe Yao; Tingkui Wu; Hao Liu; Kangkang Huang; Junbo He; Shihao Chen; Beiyu Wang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Contiguous two-segment cervical disc arthroplasty (CDA) is safe and effective, while post-operative radiographic change is poorly understood. We aimed to clarify the morphological change of the three vertebral bodies operated on. Methods Patients admitted between 2015 and 2020 underwent contiguous two-level Prestige LP CDA were included. The follow-up was divided into immediate post-operation (≤ 1 week), early (≤ 6 months), and last follow-up (≥ 12 months). Clinical outcomes were measured by Japanese Orthopedic Association (JOA) score, visual analogue score (VAS), and neck disability index (NDI). Radiographic parameters on lateral radiographs included sagittal area, anterior-posterior diameters (superior, inferior endplate length, and waist length), and anterior and posterior heights. Sagittal parameters included disc angle, Cobb angle, range of motion, T1 slope, and C2-C7 sagittal vertical axis. Heterotopic ossification (HO) and anterior bone loss (ABL) were recorded. Results 78 patients were included. Clinical outcomes significantly improved. Of the three operation-related vertebrae, only middle vertebra decreased significantly in sagittal area at early follow-up. The four endplates that directly meet implants experienced significant early loss in length. Sagittal parameters were kept within an acceptable range. Both segments had a higher class of HO at last follow-up. More ABL happened to middle vertebra. The incidence and degree of ABL were higher for the endplates on middle vertebra only at early follow-up. Conclusion Our findings indicated that after contiguous two-segment CDA, middle vertebra had a distinguishing morphological changing pattern that could be due to ABL, which deserves careful consideration before and during surgery.